Effect of coverage on the magnetic properties of –COOH, –SH, and –NH2 ligand-protected cobalt nanoparticles. Issue 27 (30th June 2021) - Farkaš, Barbara; de Leeuw, Nora H.
Abstract : DFT simulations predict the choice of ligand and density coverage as powerful strategies to tune anisotropy of protected cobalt nanoparticles. Abstract : Implementation of magnetic nanoparticles in biomedicine requires their passivation, which often comes at a cost of diminished magnetic properties. For the design of nano-agents with targeted magnetic behaviour, it is important to distinguish between ligands which can improve desired performance, and those that reduce it. Carboxylic acid-, thiol-, and amine-protected cobalt nanoparticles were studied by density functional theory calculations to model the impact of ligand coverage on the magnetic properties. The simulations show that the functional group, arrangement, and coverage density of the ligand coating control both the total magnetic moment and magnetic anisotropy energy of the nanoparticle, as well as the distribution of local spin magnetic moments across the metallic core. Captured effects of ligand binding on the orbital moments of cobalt atoms were insignificant. Out of the three ligand families, only carboxylic acid coatings increased the magnetic moments of cobalt nanoparticles, while amines and thiols quenched them. Calculated anisotropy energies of protected nanoparticles consistently increased with the growing ligand density, reaching the highest values for a 100% coverage of both carboxylic acid and thiol coatings. However, the binding nature of the two functional groups showed opposite impacts on the d-states of interacting cobalt atoms. This study has thus established important principles for the design of biocompatible magnetic nanocomposites, highlighting different routes to achieve desired magnetic behaviour.